PROGRAM TAHFIDZ ALQURAN DI SEKOLAH (STUDI KASUS MAN 2 KOTA MALANG) - Devara Risky Aprilyanto; Sultoni Sultoni; Ali Imron; Imron Arifin (STKIP Pesisir Selatan, 2026)
This study aims to analyze comprehensively the management of the Al-Qur’an memorization (tahfidz) program at MAN 2 Malang City, focusing on program planning, implementation, supervision, memorization strategies, indicators of success, and institutional strategies in addressing implementation challenges within a formal madrasah setting. This research employed a qualitative descriptive approach with a case study design. Data were collected through in-depth interviews with the principal, tahfidz coordinator, teachers, and students, supported by direct observation and document analysis. Data analysis followed the Miles and Huberman interactive model, including data condensation, data display, and conclusion drawing, while triangulation techniques were applied to ensure validity and credibility. The findings indicate that the tahfidz program is systematically designed and aligned with the madrasah’s vision and mission. Implementation integrates structured memorization methods, particularly tikrar and muraja’ah, accompanied by continuous supervision and periodic evaluation. Program success is reflected in the achievement of memorization targets, accuracy in tajwid application, consistency in muraja’ah, and the strengthening of students’ religious character. The study offers novelty by presenting a holistic educational management perspective that integrates managerial functions with character formation in a public madrasah context.